Malaysian motorcyclists behavior contributing road traffic crashes (RTCs) / Mohd Arzaimiruddin Ariffin - Ariffin, Mohd Arzaimiruddin (2010)
Total number of road accident in Malaysia exceeded 363,314 in year 2007 alone and average person died from this road accident every single day were 17 persons. Although much effort has been devoted to the study of road accidents in Malaysia, it is only until recently little attention had been given to the accidents involving motorcycles. Lacks of attention, reckless driving, lack of proper protection, speeding and bad personal habit are some of the general problems that cause of accidents. This research was undertaken to study Malaysian Motorcyclists Behavior Contributing Road Traffic Crashes (RTCs). Three methods of data collection have been done by distribution the questionnaires to the UiTM students using flyers and emails, interview with a police officer, and an observation at one location which always accidents occurred, at Bulatan Bistari, Section 2, Shah Alam. The observation was carried out at two peak hours, 8.10 am – 9.10 am and 4.15 pm – 5.15 pm. These data of 3 methods show that human behavior is a main cause of motorcycle accidents and then followed by another factors such as environmental, mechanical defects, and riding experience. Besides that, the most risk involved in accidents is male due to egos, desiring to try new things, and others bad behavior.